2011
DOI: 10.1111/j.1447-0756.2010.01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Triple flap vaginoplasty for agenesis of the vagina

Abstract: A three flap method of vaginoplasty in agenesis of the vagina has been described with good result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…1e3 Borsellino et al reported that three of 56 patients (5.3%) had a recurrent buried penis after surgery. 1 Frenkl et al reported a recurrence rate of 11.5e14.3% after a standardized surgical approach (fixation of the subcutaneous penile skin at the base of the degloved penis to Buck's fascia of the penile shaft). 2 There have been no previous reports of traction and fixation after surgery for a buried penis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1e3 Borsellino et al reported that three of 56 patients (5.3%) had a recurrent buried penis after surgery. 1 Frenkl et al reported a recurrence rate of 11.5e14.3% after a standardized surgical approach (fixation of the subcutaneous penile skin at the base of the degloved penis to Buck's fascia of the penile shaft). 2 There have been no previous reports of traction and fixation after surgery for a buried penis.…”
Section: Discussionmentioning
confidence: 98%
“…In the UK, studies have shown that 70% of households have internet access and 42% of adults had used the internet to seek healthrelated information. 1 While the internet may be an unequivicol method by which knowledge and information can be distributed and shared, numerous studies have demonstrated that the information present can be ambiguous and disingenuous not to mention inaccurate. We recently reviewed the quality of Internet-based information on three common hand pathologies: Dupuytren's disease, carpal tunnel syndrome and trigger finger.…”
Section: Nobuyuki Mitsukawamentioning
confidence: 99%
See 1 more Smart Citation
“…However, skin grafts in the neovagina have been criticized due to the high rate of contracture and stenosis of the vaginal orifice. 1,2 We describe a patient who had stenosis of the distal vagina and vaginal orifice after McIndoe operation. Using a posterior labial perforator based island flap we achieved a satisfactory result.…”
mentioning
confidence: 99%
“…5 Because of their abundant blood supply, proximity to the defect and similarity of tissue characteristics, several perineal flaps have been suggested. 1,2 The perforator from the posterior labial artery originates from the posterior labial artery within 1.5 cm of the posterior margin of the labium, and extends antero-laterally through deep fascia to the posteriolateral base of the labia majora. It gives off at least three to five branches and supplies the inferior perineal regions.…”
mentioning
confidence: 99%